Government instruments for community renewable energy in northern and Indigenous communities. (June 2023) - Leonhardt, Renata; Noble, Bram; Poelzer, Greg; Belcher, Ken; Fitzpatrick, Patricia
Abstract: Energy insecurity is part of everyday life for many remote and Indigenous communities across the North. Community energy is emerging as a solution to address enduring energy challenges in remote regions, but the success of community energy initiatives hinges, in part, on adequate and accessible government instruments. Formal policies and rules to advance energy transition play an essential role in community energy, yet there is limited understanding of government instruments to support community energy in northern and Indigenous communities. This paper provides a critical assessment of government instruments for community energy in northern, remote, and Indigenous communities in Canada. Based on interviews with 48 actors engaged in northern community energy, results show a range of available instruments. While each serves different functions, financial supports and community ownership instruments emerge as dominant needs for community energy in the North. However, many northern and remote Indigenous communities lack the capacity to access supports when they are available, are competing against each other for limited resources, or are constrained by the rules and regulations of traditional and centralized energy ownership systems. A diversity of complimentary and reinforcing instruments is essential, sensitive to community needs, capacities, and aspirations. Highlights: Government instruments are essential for community energy remote northern communities. Financial supports and community ownership are core to community energy in the North. Many northern and remote Indigenous communities lack the capacity to access supports. Northern community energy is constrained by centralized energy utility ownership. Complimentary instruments are needed, sensitive to community needs and capacities.